(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
A submerged turbulent plane jet in shallow water impinging vertically onto the free surface will produce a large-scale flapping motion when the jet exit velocity is larger than a critical one. The flapping phenomenon is verified in this paper through a large eddy simulation where the free surface is modeled by volume of fluid approach. The quantitative results for flapping jet are found to be in good agreement with available experimental data in terms of mean velocity, flapping-induced velocity and turbulence intensity. Results show that the flapping motion is a new flow pattern with characteristic flapping frequency for submerged turbulent plane jets, the mean centerline velocity decay is considerably faster than that of the stable impinging jet without flapping motion, and the flapping-induced velocities are as important as the turbulent fluctuations.